Prevalence of Upper Limb Length Discrepancy among Asymptomatic Population of Medical Students in Nepal: A Descriptive Cross Sectional Study - Nitasha Sharma; Chet Kanta Bhusal; Ruku Pandit (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Upper limb length discrepancy are frequently documented in various anatomical orthopedics and anthropometric journals. Proper idea about discrepancy is pivotal prior to any limb lengthening surgery. The aim of the study is to ﬁnd out the prevalence of upper limb length discrepancy among asymptomatic population in medical students of Nepal. MATERIAL AND METHODS A descriptive cross-sectional study was carried out at the department of anatomy in Universal College of Medical Sciences, Bhairahawa, Nepal from September 2021 to November 2022 after ethical clearance from the same institution (IRC UCMS, Ref: UCMS/IRC/079/21). Full and segmental length of upper limb was taken, recorded with help of ﬂexible tape. Reference points for these measurements were bony landmarks as approved in the Integrative Measurement Protocol Morphological and Behavioral Research in Human and non-human primates version 1.0 were used. Convenient sampling method was used Data was analyzed using Microsoft Excel 2016. Point estimate at 95% Conﬁdence Interval was calculated along with frequency and percentage. RESULTS Out of two hundred ﬁfty seven participants 141 were male and 116 were female. Total upper limb length of male is 74.17± 4.79 cm and female is 71.92 ± 4.81cm. Total upper limb length discrepancy maximum was observed 3 cm. In our study it was observed that wrist has maximum discrepancy between right and left limb followed by arm and fore arm. CONCLUSION The present study shows the prevalence of upper limb length discrepancy in asymptomatic Nepalese population.